2022
DOI: 10.2337/db21-1093
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Metabolomic Markers in Early to Mid-pregnancy for Gestational Diabetes Mellitus: A Prospective Test and Validation Study

Abstract: Gestational diabetes (GDM) predisposes pregnant individuals to perinatal complications and long-term diabetes and cardiovascular diseases. We developed and validated metabolomic markers for GDM in a prospective test-validation study. In a case-control sample within the PETALS cohort (91 GDM, 180 non-GDM; discovery set), a random PETALS subsample (42 GDM, 372 non-GDM; validation set 1), and a case-control sample within the GLOW trial (35 GDM, 70 non-GDM; validation set 2), fasting serum untargeted metabolomics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The levels of metabolites were log-transformed (base 10) and mean-centred and divided by the standard deviation of each variable. The least absolute shrinkage and selection operator (LASSO) regression using a 10-fold cross-validation was used to select the most predictive metabolites to EA ( Zhu, et al, 2022 ). The selection was judged from the lambda with 1 SE of the minimum partial likelihood of deviance.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of metabolites were log-transformed (base 10) and mean-centred and divided by the standard deviation of each variable. The least absolute shrinkage and selection operator (LASSO) regression using a 10-fold cross-validation was used to select the most predictive metabolites to EA ( Zhu, et al, 2022 ). The selection was judged from the lambda with 1 SE of the minimum partial likelihood of deviance.…”
Section: Methodsmentioning
confidence: 99%
“…Amino acid metabolic products, in particular, tyrosine and tryptophan metabolites have been shown to have an impact on GLP-1 synthesis [ 107 ]. The decreased levels of indole compounds, metabolites derived from tryptophan through microbial decarboxylation and dehydrogenation reactions, in maternal serum during early and mid-gestation are associated with an increased risk of GDM [ 108 ], which may be attributed to reduced populations of tryptophan-metabolizing bacteria like Bifidobacterium [ 87 ] and Lactobacillus [ 88 ] in the gut microbiota of GDM patients, consequently leading to impaired synthesis of indole-3-propionic acid and secretion of incretins like GLP-1 and GLP-2, further aggravating insulin resistance in GDM [ 109 ]. Furthermore, γ-aminobutyric acid can affect insulin sensitivity through the GPR41/43 pathway [ 65 ].…”
Section: Microbial Metabolites In Gdmmentioning
confidence: 99%
“…Zhu et al. ( 58 ) explored metabolomics markers and developed a panel for the early diagnosis of GDM, which paved the way for clinical practice. Time-of-flight GC-MS was performed in cohorts from three population-based studies conducted by different centers, which included 168 patients with GDM and 622 normal controls.…”
Section: Early Diagnosis Of Gestational Diabetes Mellitus By Metabolo...mentioning
confidence: 99%
“…Finally, Zhu et al. ( 58 ) found that a 17-metabolite panel at 10–13 weeks of gestation and a 13-metabolite panel at 17–19 weeks of gestation outperformed the model using conventional risk factors, including fasting glycemia.…”
Section: Early Diagnosis Of Gestational Diabetes Mellitus By Metabolo...mentioning
confidence: 99%